Extremely high corrosion resistance of ZnxNi1–xCr2O4 spinel as sidewalls in the aluminum electrolyte. Issue 6 (June 2023) - Ge, Bangzhi; Liu, Rongdi; Wei, Zhilei; Wang, Ke; Shi, Zhongqi
Abstract: The sidewall material is a key component in new electrolytic cell with an inert electrode for the aluminum electrolysis industry. The continuous development of novel sidewall materials with excellent corrosion resistance in molten salts electrolyte is an important topic. Herein, a new system of sidewall material, spinel structured Zn x Ni1– x Cr2 O4 ( x = 0 – 1), is prepared by solid-phase reaction and the corrosion-resistance enhancement is investigated. The results prove that Zn 2+ plays two roles in the Zn x Ni1– x Cr2 O4 spinels. Firstly, Zn 2+ tunes the surface energies of spinels resulting in the octahedral grains, which suppresses the cation diffusion in the corrosion process. Secondly, Zn 2+ stabilizes the Cr 3+ in the spinels. As a result, the Zn0.5 Ni0.5 Cr2 O4 spinel displays an extremely low corrosion rate ∼0.007 cm·a –1 in NaF-KF-AlF3 bath at 800 °C comparing with other sidewall materials. The as-obtained spinel shows great potential as a novel sidewall material for the new electrolytic cell.